Perancangan Kinerja Kepala Sekolah Menengah Atas dalam Perspektif Balanced Scorecard (BSC) Menggunakan Analytical Network Process (ANP) (Studi Kasus : SMA ABC Jakarta) - Sahar, Rahmah Laila; Chirzun, Ahmad (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2022)
Education in the sense of schooling is now leading to the process of industrialization. The world of education can no longer be considered as a social institution only but must be treated industrially, which is treated or managed professionally. Due to the increasingly fierce world of competition today, if educational institutions are not managed professionally, then the customer will leave educational institutions if they are poorly managed. In various case studies, the Balanced Scorecard has provided many benefits to the development of education management, especially SMA ABC Jakarta does not yet have a performance measurement based on the Balanced Scorecard method. In the Balanced Scorecard method, the measurement is based on four perspectives, namely, financial, customer, internal business processes, and growth and learning perspectives. Therefore, a good performance design needs to be done to realize the vision of this ABC Jakarta High School. So, a performance design was carried out for the Principal of SMA ABC Jakarta using the perspective of the Balanced Scorecard method. Then, the weighting and prioritization of each KPI are carried out using the Analytical Network Process with the help of Super Desicion software. The results of this study are in the form of a Scorecard List, and there are 13 Principal KPIs from each perspective, namely 1 KPI from a Financial perspective, 9 KPIs from an Operational perspective, 2 KPIs from a Customer perspective, and 1 KPI from an HR perspective. Then, for the priority results of this KPI, it is found in the operational perspective, precisely on the KPI for the Implementation of Supervision of the Learning Process by Schools or O9 with a weight of 0.1992 or in the percentage of 20%, this indicates that the Implementation of Supervision of the Learning Process by Schools is the most important thing. compared to other KPIs.Keywords - Analytical network process, Balanced scorecard, Perancangan kinerja, Software super decision.